A study on the efficiency of different tongue cleaning methods - Picornell, Mara Bianca V.
The oral cavity is one of the most astounding parts of the body. We use it everyday for conversing and masticating among some and when giving oral health instructions to the patients, the importance of tongue hygiene is often overlooked or neglected by the dentist. Negligence of tongue hygiene has found to be a contributor to the development of caries and periodontal disease, increase in halitosis and decrease in taste acuity. The study aims to determine the more efficient tongue cleaning method, comparing a toothbrush and a tongue scraper, in terms of decrease in Colony Forming Units (CFU) in three (3) different dilutions and patient's preference. T-Test results show that there is a significant difference in the number of CFU in dilution 1:1,000 and 1:10,000 in favor of using a tongue scraper and no significant difference in the number of CFU in dilution 1:100,000. Most of the subjects preferred the use of a tongue scraper in terms of effectivity, ease of use, while most of the subjects preferred the toothbrush in terms of comfort. Therefore, the tongue scraper is more efficient in cleaning the tongue, considering that it effectively removes tongue debris as proven in the dilution 1:1,000 and is more popularly chosen by the subjects.